Motivational Interviewing for Maternal Immunisation (MI4MI) study: a protocol for an implementation study of a clinician vaccine communication intervention for prenatal care settings. Issue 11 (17th November 2020) - Brewer, Sarah E.; Cataldi, Jessica R.; Fisher, Mary; Glasgow, Russell E.; Garrett, Kathleen; O'Leary, Sean T.
Abstract : Introduction: Vaccination against influenza and pertussis in pregnancy offers a 'two-for-one' opportunity to protect mother and child. Pregnant patients have increased risk of severe disease from influenza and newborns have increased risk of severe disease from both influenza and pertussis. Obstetricians need communication tools to support their self-efficacy and effectiveness in communicating the importance of immunisation during pregnancy and ultimately improving maternal vaccination rates. Methods and analysis: We describe the protocol for a pragmatic study testing the feasibility and potential impact of a clinician communication strategy on maternal vaccination uptake. This study will be conducted in five prenatal care settings in Colorado, USA. The Motivational Interviewing for Maternal Immunisation strategy involves training prenatal care providers to use motivational interviewing in the vaccine conversation with pregnant patients. Our primary outcomes will be the adoption and implementation of the intervention measured using the Enhanced RE-AIM/Practical Robust Implementation and Sustainability Model for dissemination and implementation. Secondary outcomes will include provider time spent, fidelity to Motivational Interviewing and self-efficacy measured through audio recorded visits and provider surveys, patients' visit experience based on audio recorded visits and follow-up interviews, and maternal vaccine uptake as measured through chart reviews. Ethics and dissemination: This study is approved by the following institutional review boards: Colorado Multiple Institutional Review Board. Results will be disseminated through peer-reviewed manuscripts and conference presentations. Trial registration number: NCT04302675 .